Regeneration of Cattleya Amazing Thailand in ½ MS Medium with The Addition of Several Concentration of PGR and Coconut Water - Asnul Fitria; Zozy Aneloi Noli; Djong Hon Tjong (Jurnal Biologi Tropis, 2023)
One of the Cattleya species with aesthetic and commercial value is Cattleya Amazing Thailand. An efficient protocol with a high rate of plantlet regeneration is through in vitro culture. Plantlet regeneration is affected by the addition of a Plant Growth Regulator (PGR). Auxin and cytokinin (2,4-D and BAP) combined with PGR from organic material such as coconut water can increase the growth of leave and roots in plantlet regeneration. The research aims to determine the best PGRs combination in regenerating the  Cattleya Amazing Thailand orchid in vitro. The research used the Completely Randomized Design (CRD) experimental method for five treatments. The parameter are survival rate, number of leave, and number of roots. Survival rate was analyzed descriptively and both of number of leave and roots were analyzed statistically. All treatments can form 100% plantlets on survival rate parameter. The treatment of 0.1 mg/L 2,4-D + 1 mg/L BAP gave significantly different results in the number of leaf (9.0) and was not significantly different in the number of root. 0.1 mg/L 2,4-D + 1 mg/L BAP is the best combination for in vitro regeneration of the Cattleya Amazing Thailand orchid.